Improvement of alpha- and beta-amylase enzymes activities and germination indices in safflower variety (Carthamus tinctorius L.) seeds by foliar application of silicon and nickel in saline soil - Mahboobe Bahrami; Mohamad Rahim Owji; farhad mohajeri; Mahmood Dejam (علوم و فناوری بذر ایران)
Salinity stress reduces seed quality, but suitable concentrations of silicon and nickel can improve germination indices in the produced seeds. This study was conducted in a factorial arrangement based on randomized complete block design (RCBD) in 2018 in Haji Abad city, Hormozgan, Iran. The experimental treatments consisted of four safflower varieties as the first factor, including Soffeh, Local Isfahan, Padideh, and Golmehr; and seven spraying levels, including nickel (100, 200 and 300 mg L-1) and silicon (100, 150, and 200 mg L-1) as the second factor. The results demonstrated that the foliar application of 100 mg/l Nickle and 200 mg/l silicon increased potassium by 10% and 18%, respectively. The foliar application of 200 mg/l silicon increased the activity of alpha and beta amylase enzymes by 17% and 12%, respectively. In addition, Golmehr and Safe varieties obtained from a mother plant recorded higher germination and rate percentage, as well as seed vigor, while Padideh variety showed the lowest values of the same traits. The foliar application of 200 mg/l silicon, compared to the control, increased the seed vigor as well as Soffeh and Golmehr cultivars by 23% and 25%, respectively; however, the Nickle concentration of 300 mg/l resulted in a decrease of 24% and 19% in these cultivars.On the other, this trait decreased with increasing nickel concentration significantly. Generally, foliar application of silicon at concentrations of 150 and 200 mg L-1 was found to improve seed quality of different safflower varieties under salinity stress.